Data Management support for CGIAR - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
CCAFS has revised its data management guidelines, which were taken up/ adapted by CIAT for the Center. IITA has indicated interest to also adapt and build on them since. This will be used and useful to program and center partners for better quality, improve management of the data generated through their research.